Pengaruh Pemberian Terapi Musik Instrumen Suling Balawung terhadap Kecemasan pada Ibu Hamil Trimester III - Sofia Mawaddah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
The anxiety of pregnant women will increase when gestational age enters the third trimester; increased anxiety is associated with the proximity of the baby's birth. Anxiety is an emotional state with no specific object. This condition is experienced subjectively—this study on overcoming anxiety using one of the non-pharmacological therapies, namely music therapy. Instrumental music therapy is one of the effective distraction techniques and is believed to reduce physiological pain, stress, and anxiety by diverting one's attention. This study aimed to determine the effect of giving balawung flute music therapy on anxiety in third-trimester pregnant women. The research design used was a quasi-experimental design using one group pretest-post-test. This research was conducted from January to March 2020. The respondents of this study were pregnant women with a gestational age of TM III, totaling 20 respondents. This study used one intervention group. The intervention given was in the form of music therapy for the balawung flute instrument. This intervention was provided with a frequency of 1 time a day, 30 minutes for 14 days. Anxiety assessment on respondents was carried out before (pre-test) and after (post-test) the intervention using the HARS (Hamington Rating Scale for Anxiety) scale. The results showed that before being given musical therapy, the flute balawung instrument with mild anxiety levels was two people (20%), while pregnant women with moderate anxiety levels were eight people (8%). Pregnant women who were given the intervention with no anxiety levels as many as two people (20%), and pregnant women with mild anxiety levels amounted to 8 people (80%). The study results showed that there was an effect of music therapy on the balawung flute instrument on anxiety in third trimester pregnant women in PMB Y, Palangka Raya city.